Risk Factors and Prognosis of Early Recurrence in Stage I–II Endometrial Cancer: A Large-Scale, Multi-Center, and Retrospective Study - Dou, Yingyu; Song, Kun; Fu, Yu; Shen, Yuanming; Zhang, Chuyao; Yao, Shuzhong; Xu, Congjian; Xia, Min; Lou, Ge; Liu, Jihong; Lin, Bei; Wang, Jianliu; et al. (Frontiers in Medicine, 2022)
Abstract Objective: The aim of the present study was to determine overall survival (OS) and risk factors associated with early recurrence in patients with FIGO I-II stage endometrial carcinoma (EC). Method: Clinical features were retrospectively extracted from the database of China Endometrial Cancer Consortium from January 2000 to December 2019. A total of 2974 FIGO I-II stage endometrial cancer patients were included. Kaplan-Meier survival analysis was used to assess OS and disease-specific survival. Cox proportional hazard model and Fine & Grey was used to determine the factors related to OS. Binary logistic regression model was used to determine independent predictors of early relapse patients. Results: Of these 2974 EC, 189 patients were confirmed to have relapse. The 5-year OS was significantly different between the recurrence and non-recurrence patients (p<0.001). Three quarters of the relapse patients were reported in 36 months. The 5-year OS for early recurrence patients was shorter than late recurrence (relapse beyond 36 months, p<0.001). The grade 3 (OR=1.55, 95%CI 1.17-2.05, p =0.002) ,LVSI and more than half of depth of myometrial infiltration (OR=3.36; 95%CI 1.50-7.54,p =0.003; HR=2.07, 95%CI1.17-3.65, p =0.012) were independent risk factors of early relapse. The protective factor of that is PR-positive (OR=0.50, 95%CI 0.27-0.92, p=0.02). Bilateral ovariectomy could reduce recurrence risk rate (OR=0.26, 95%CI 0.14-0.51, p<0.001). Conclusion: The OS of early relapse EC is worse. Grade3, LVSI and more than half of depth of myometrial infiltration are independent risk factors for early relapse EC. And the protective factor is ER-positive for those people. Bilateral salpingo-oophorectomy could reduce the risk of recurrence.